Northern Ireland life and times survey, 2021 - Devine, Paula (Northern Ireland life and times survey, 2022)
The Northern Ireland Life and Times Survey (NILT) series began in 1998, and was the successor to the previous Northern Ireland Social Attitudes series, which was discontinued in 1996. Previous NILT surveys had been undertaken as a face-to-face interview, followed by a short self-completion questionnaire. However, due to the COVID-19 pandemic, the 2020 and 2021 surveys were undertaken online. Respondents could also request to complete the survey via a phone or video interview, if they desired.